Phylogenetic analysis of the genus Lensia (Cnidaria, Hydrozoa, Siphonophora), based on the species morphology - Nishiyama, Eric Y.; Ribeiro, Guilherme C.; Oliveira, Otto M. P. (Zootaxa, 2016)
Siphonophores are poorly studied despite their abundance and ecological importance in marine ecosystems. The genus Lensia Totton, 1932 contains the highest number of species within Siphonophora, but systematic studies of these organisms are scarce in the literature. This study presents a phylogenetic analysis for fifteen species of Lensia based on morphological data. The material for this study was obtained during two oceanographic campaigns made along the southeastern Brazilian coast. A total of twenty two characters of the anterior nectophore morphology were scored. The shortest trees were searched using parsimony (under different weighting regimes). All analyses provided the same topology: (M. kochi (D. dispar + D. bojani) (L. leloupi (L. havock (L. conoidea (L. subtilis; L. meteori; L. hardy; L. fowleri; (L. subtiloides (L. hotspur; L. cossack; L. campanella)); (L. multicristata (L. hunter (L. lelouveteau + L. grimaldii))). The monophyly of the genus Lensia is supported by the hydroecium measuring up to 1/4 the height of the nectosac.